2020
DOI: 10.3389/ffgc.2020.594274
|View full text |Cite
|
Sign up to set email alerts
|

Large Trees Dominate Carbon Storage in Forests East of the Cascade Crest in the United States Pacific Northwest

Abstract: Large-diameter trees store disproportionally massive amounts of carbon and are a major driver of carbon cycle dynamics in forests worldwide. In the temperate forests of the western United States, proposed changes to Forest Plans would significantly weaken protections for a large portion of trees greater than 53 cm (21 inches) in diameter (herein referred to as "large-diameter trees") across 11.5 million acres (∼4.7 million ha) of National Forest lands. This study is among the first to report how carbon storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 96 publications
8
70
0
Order By: Relevance
“…In contrast, volume (and therefore carbon) shows the smallest increment in the first 50 years and the biggest in the 50-yr epoch between 100 and 150 years. This superior carbon sequestration in older trees is consistent with recent reports of recent rapid sequestration of older oak trees in Massachusetts (Finzi et al, 2020) and the outsized forest accumulation in large trees (Stephenson et al, 2014;Mildrexler et al, 2020). Here, the largest pine measured in Massachusetts (by volume) achieved 6.62 tC at 190 years old, and we found very large pines at ages ranging up to 350 years at dozens of sites in the Eastern United States.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, volume (and therefore carbon) shows the smallest increment in the first 50 years and the biggest in the 50-yr epoch between 100 and 150 years. This superior carbon sequestration in older trees is consistent with recent reports of recent rapid sequestration of older oak trees in Massachusetts (Finzi et al, 2020) and the outsized forest accumulation in large trees (Stephenson et al, 2014;Mildrexler et al, 2020). Here, the largest pine measured in Massachusetts (by volume) achieved 6.62 tC at 190 years old, and we found very large pines at ages ranging up to 350 years at dozens of sites in the Eastern United States.…”
Section: Discussionsupporting
confidence: 92%
“…To avoid ever more serious consequences of a changed climate, the goal must be to become net carbon negative as soon as possible. Growing suitable existing forests is an effective and low cost means for reducing the atmospheric stock of carbon as others have noted (Fargione et al, 2018;Hudiburg et al, 2019;Moomaw et al, 2019;Mildrexler et al, 2020) and will be demonstrated by the findings reported in this paper. Natural regeneration of forests has recently been found to accumulate more carbon in the first 30 years than managed reforestation (Cook-Patton et al, 2020).…”
Section: Introductionsupporting
confidence: 62%
“…Because large trees dominate carbon storage in natural forests (Mildrexler, Berner, and Law et al 2020), and trees are generally larger in natural forests than plantations, such loss of natural forest cover would hugely reduce carbon storage capacity. We showed that Xishuangbanna's rapid land use change has also reduced its overall ability to store carbon.…”
Section: Discussionmentioning
confidence: 99%
“…This policy change is designed to allow cutting of young (<150 years) shade-tolerant fir ≥53 cm DBH to facilitate the conservation and recruitment of old (>150 years) shade-intolerant pine and larch (United States Department of Agriculture (USDA) Forest Service, 2020). Mildrexler et al (2020) criticize this proposal based solely on evidence that large trees (i.e., trees ≥53 cm DBH) store more carbon than small trees (i.e., trees <53 cm DBH). Without any analysis of tree-, stand-, or landscape-scale carbon fluxes, Mildrexler et al argue that forest-based climate change mitigation goals can best be served by maintaining prohibitions on cutting young trees ≥53 cm or even extending prohibitions to include trees as small as 30 cm DBH.…”
Section: Introductionmentioning
confidence: 99%
“…The errors, oversights, and misrepresentations in Mildrexler et al summarized below and in Table 1 make this study an unsuitable basis for evaluating policy change. Mildrexler et al (2020).…”
Section: Introductionmentioning
confidence: 99%